1975
DOI: 10.1073/pnas.72.2.508
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical studies on golgi apparatus, GERL, and lysosomes in neurons of dorsal root ganglia in mice.

Abstract: Cytochemically demonstrable thiamine pyrophosphatase activity is present in the innermost Golgi element in both small and large neurons of the dorsal root ganglia in CF1, C57 black, and C57 beige mice, thus resembling the neurons of rat dorsal root ganglia. The localization of acid phosphatase (EC 3.1.3.2) activity in the large neurons of dorsal root ganglia in these mice is also similar to that in rats; it is not demonstrable in Golgi elements but is present in GERL and in three types of lysosomes apparently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1976
1976
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 13 publications
2
18
1
Order By: Relevance
“…The Golgi complex shown in the present study is different from those reported in other tissues which are relatively isolated structures from each other (2,14,16,(20)(21)(22)(23)(24) : in human and mouse cultured fibroblasts the stacks of the cisternal part of the Golgi complex are relatively isolated from each other, while the continuous network of the reticular part exists as if it combines the isolated cisternal parts, thus integrating the whole Golgi complex as a single elaborate network system. Although Novikoff et al (2 1) once suggested that the GERL is a continuous structure throughout the cytoplasm, they did not show any persuasive pictures .…”
Section: Monolayer Cell Ultracytochemistrycontrasting
confidence: 54%
See 2 more Smart Citations
“…The Golgi complex shown in the present study is different from those reported in other tissues which are relatively isolated structures from each other (2,14,16,(20)(21)(22)(23)(24) : in human and mouse cultured fibroblasts the stacks of the cisternal part of the Golgi complex are relatively isolated from each other, while the continuous network of the reticular part exists as if it combines the isolated cisternal parts, thus integrating the whole Golgi complex as a single elaborate network system. Although Novikoff et al (2 1) once suggested that the GERL is a continuous structure throughout the cytoplasm, they did not show any persuasive pictures .…”
Section: Monolayer Cell Ultracytochemistrycontrasting
confidence: 54%
“…They considered the GERL the site of the formation of lysosomes of various types (2,16,19) and also of secretory granules of various kinds (20,22,23). In the present study on cultured fibroblasts, it was also suggested that the reticular part of the Golgi complex (GERL) is the site of the formation of primary lysosomes of two types, the coated vesicle type and the regular dense body type.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, only 22% of the total TPPase activity is present in fraction B (Tables II and III). It should also be noted that TPPase has been shown to be a marker for Golgi membrane only in noncultured cells (7) and that its use as a Golgi marker in this study is based on inference. On the other hand, 5'-nucleotidase and Na +, K+-ATPase have been reported to be plasma membrane markers in cultured CEF (4,43).…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen was purified from fetal bovine serum or chicken serum by two passages over a lysine sepharose affinity column (47). The incubation mixture (1.0 ml) contained [5][6][7][8][9][10] /~g of purified plasminogen, 0.1 M Tris (pH 8.1), 0.02% Triton, and an aliquot of an RSV-CEF subcellular fraction (1-10 /zg protein). Aliquots were removed from duplicate petri dishes at 1, 2, and 3 h during incubation at 37~ and the radioactivity released was determined directly in an Intertechnique gamma counter (Intertechnique, Fairfield, N.J .).…”
Section: Enzyme Assaysmentioning
confidence: 99%